Um Sistema Hiperbólico Acoplado Envolvendo o Operador p-Laplaciano - Carvalho, Pitágoras Pinheiro de (2010)
Our goal in this work is to study the existence of weak solutions for the coupled system, in the form: 8> ><>>: u00 + Au --- u0 + --jvj-+2 + jzj-+2-juj- u = f1 v00 + Av -- -v0 + --juj-+2 + jzj-+2-jvj- v = f2 z00 + Az -- -z0 + --juj-+2 + jvj-+2-jzj- z = f3 ; em Q; com, Q = (0; T)- with, Q = (0; T) - where (0; T) is a real line, an open, limited and regular of R3; and - = 3 Xj=1 @2 @x2 j is the Laplacian operator.